2013
DOI: 10.1177/0018726712469548
|View full text |Cite
|
Sign up to set email alerts
|

Identity undoing and power relations in leadership development

Abstract: Leadership development theory and practice is increasingly turning its gaze on identity as a primary focus for development efforts. Most of this literature focuses on how the identities of participants are strengthened, repaired and evolved. This article focuses on identity work practices that are underdeveloped in the literature: the deconstruction, unravelling and letting go that can be experienced when working upon one’s self. We group these experiences, among others, under the conceptual term ‘identity und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(186 citation statements)
references
References 64 publications
4
162
0
2
Order By: Relevance
“…But this general attitude towards openness in encounter with the other could also be argued to relate to the process of dialogue. Similar connections between dialogue and the event of interpretation can be found in studies that emphasize the need for leaders to undertake continuing reflective work on their self-understanding, as they weave together their interpretations gained through connection with others with whom their experiences have been entangled (Nicholson & Carroll, 2013;Sparrowe, 2005).…”
Section: Interpretation Of Experience In Leadership Development Litermentioning
confidence: 59%
“…But this general attitude towards openness in encounter with the other could also be argued to relate to the process of dialogue. Similar connections between dialogue and the event of interpretation can be found in studies that emphasize the need for leaders to undertake continuing reflective work on their self-understanding, as they weave together their interpretations gained through connection with others with whom their experiences have been entangled (Nicholson & Carroll, 2013;Sparrowe, 2005).…”
Section: Interpretation Of Experience In Leadership Development Litermentioning
confidence: 59%
“…In addition, Muller, Alliata and Benningh (2009) assert that teachers derive satisfaction from the higher social needs like self-esteem and social relations. When teachers get opportunities to be promoted to the leadership position, their practices are legitimized and give rise to a new teacher professional identity (Nicholson and Carroll, 2013). Nevertheless, studies have found that some people come to the teaching profession as a last resort career (Ejieh, 2009); as teaching particularly ESL/EFL teaching is not among the established careers.…”
Section: Practical and Pragmatic Aspects Of Teacher Identitymentioning
confidence: 99%
“…While the participants indicated that the respondents would like to be EFL teachers; however, some participants perceive their future selves as administrators or teacher trainers. This suggests that the leadership repertoire helped the participants engage in an endeavor of undoing their previous professional identities (Nicholson & Carroll, 2013) which ultimately led to the reshaping of new professional identities.…”
Section: Efl Teachers and Their Future Selvesmentioning
confidence: 99%
“…The leader may get trapped in the dynamics of 'betwixt and between', where they feel stuck between the identity of who they were in their previous role and who they need to be in their new role (Bandow & Self, 2016;Freedman, 2011;Nicholson & Carroll, 2013). Similarly, Boal (2000) argued that a leader will transition through six phases, which include the honeymoon, learning curve, constant, random, null and lastly rigor mortis.…”
Section: The Nature Of the Transitionmentioning
confidence: 99%